Orthographic Depth and Its Impact on Universal Predictors of Reading - Ziegler, Johannes C.; Bertrand, Daisy; Tóth, Dénes; Csépe, Valéria; Reis, Alexandra; Faísca, Luís; Saine, Nina; Lyytinen, Heikki; Vaessen, Anniek; Blomert, Leo (Psychological Science, 2010)
Alphabetic orthographies differ in the transparency of their letter-sound mappings, with English orthography being less transparent than other alphabetic scripts. The outlier status of English has led scientists to question the generality of findings based on English-language studies. We investigated the role of phonological awareness, memory, vocabulary, rapid naming, and nonverbal intelligence in reading performance across five languages lying at differing positions along a transparency continuum (Finnish, Hungarian, Dutch, Portuguese, and French). Results from a sample of 1,265 children in Grade 2 showed that phonological awareness was the main factor associated with reading performance in each language. However, its impact was modulated by the transparency of the orthography, being stronger in less transparent orthographies. The influence of rapid naming was rather weak and limited to reading and decoding speed. Most predictors of reading performance were relatively universal across these alphabetic languages, although their precise weight varied systematically as a function of script transparency.